Historical development of Islamic venture capital: an appraisal - Hassan, Rusni; Mikail, Sa'id Adekunle; Arifin, Mahamad (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
Venture capital is commonly defined as medium to long-term equity investment provided for unlisted companies to finance their start up, expansion, survival and change of ownership. The origin of which was traced back to mudharabah; which is commonly translated to Islamic limited partnership. The application of venture capital seems to be abandoned in Muslim world for long, while Western communities get steady development of it. Since the inception of Islamic banks for almost two decades, Islamic banks are also turning a blind eye to venture capital. In spite that venture capital is akin to Islamic bank’s principle of profit and loss sharing. The first Islamic bank which was introduced 1963 at Mit Ghamr by Dr. El-Naggar, was primarily built on mudharabah contract which constitutes a tiny portion in day-to-day operations of Islamic banking and financial institutions to date due to risks associated with this area of investment. However, venture capital considered as a formidable tool for economic and technological development in the West. This study aims at studying historical development of mudharabah and musharakah that constitute the root of the modern venture capital. The study covers both classical and modern Islamic venture capital. The study finds that modern Islamic venture capital operates in form of banking and financial institution at the outset. This is could be imagined with the establishment of the first Islamic bank at Mit Ghamr Egypt 1963, Tabung Hajj at 1960s. On the contrary, Mudharabah Companies established in Pakistan in1984 operates in form of fund management company. Nevertheless, the first fund carries the tittle of Islamic venture is Injazah funds established in 2004.The first fund and management corporation dedicated for Islamic venture capital is Musharaka Venture Tech. and Management established in Malaysia 2008. The first banking institution dedicated for Islamic venture capital and private equity investment is Venture Capital Bank established in Bahrain 2006. The common Shari‘ah applicable principles are musharakah, mudharabah, and wakaalah. Although muzara’ah and musuqat are seldom applied in the agricultural sector. In a nutshell, the study provides Shari‘ah framework for Islamic venture capital and proposes solutions for pressing issues.